Effects of Multiple Representation in Student's Conceptual Understanding and Metacognitive Awareness in Mechanics - Orillo, Mark Joseph F.; Mistades, Voltaire M. (KnE Social Sciences, 2024)
Using a mixed-method design, the study investigated the effect of the use of multiple representations on 207 (106 male and 101 female) Grade 11 students’ conceptual understanding and metacognitive awareness in learning concepts in physics (mechanics). There were five multiple representations (MRs) used in this study namely: (a) drawing/sketch, (b) free-body diagram/FBD, (c) description, (d) mathematical equation, and (e) concept map (Know - Want to know - Learn). These MRs were embedded in the teacher’s lesson plan as a strategy for teaching and learning selected topics in Mechanics. All these MRs were used by the teacher to discuss each lesson, and by the students to understand and do the tasks given to them. The conceptual understanding of the students was measured by obtaining the mean scores from the formative test scores in the form of a 10-item quiz for the following topics - Kinematics, Laws of Motion, and Universal Law of Gravitation. The students’ metacognitive awareness was measured using the 52-item metacognitive awareness inventory (MAI) questionnaire, given before and after the implementation of the teaching-learning intervention. Students’ perceptions on the use of MRs were also gathered in the form of short responses to a 5-item questionnaire. Their responses to these questions were used to elaborate and explain the results in the subcategories of the MAI. Mean scores in the formative tests revealed that students obtained passing grades in all three quizzes. Results also showed that there was an increasing trend in the students’ mean scores from Quiz 1 to Quiz 3. Paired t-test also showed that the increase in the students’ scores moving from Quiz 1, Quiz 2, to Quiz 3 were significant at p < 0.05. The results of the Metacognitive Awareness Inventory (MAI) questionnaire revealed that a significant difference was observed, when comparing the students’ profile scores before and after the implementation of the teaching-learning intervention. The use of multiple representations (MRs) made the students more aware of how they think about learn the physics concepts. Keywords: multiple representation, conceptual understanding, metacognitive awareness